Method for assessment of the static strength of a two-level rotor blade of a turbofan unit - Терещенко, Ю. М.; Дорошенко, К. В.; Ластівка, І. О.; Терещенко, Ю. Ю. (Science-based technologies, 2017)
The paper presents the results of investigations for a working wheel with two-level blades made of a high-temperature alloy. A numerical experiment was used to determine the temperature field in the flow section of the turbofan unit. When calculating the strength of the two-level blades of a turbofan unit, the tensile and bending stresses by centrifugal forces, bending by gas forces, and additional temperature stresses were taken into account. Additional temperature stresses are the result of uneven heating of the blade body. Method for assessment of the static strength of two-level blades of a working wheel of a turbofan unit is proposed. The results of the evaluation of the static strength of two-level blades of the working wheel allow to clarify the calculated values of the thermogasdynamic parameters of the turbofan unit. Method can be recommended for use in calculating the parameters of gas turbine engines with the rear location of the turbofan unit.